Increased Breadth of Group A Streptococcus Antibody Responses in Children With Acute Rheumatic Fever Compared to Precursor Pharyngitis and Skin Infections . (4th February 2022) - Whitcombe, Alana L; McGregor, Reuben; Bennett, Julie; Gurney, Jason K; Williamson, Deborah A; Baker, Michael G; Moreland, Nicole J
Abstract: Background: Group A Streptococcus (GAS) causes superficial pharyngitis and skin infections as well as serious autoimmune sequelae such as acute rheumatic fever (ARF) and subsequent rheumatic heart disease. ARF pathogenesis remains poorly understood. Immune priming by repeated GAS infections is thought to trigger ARF, and there is growing evidence for the role of skin infections in this process. Methods: We utilized our recently developed 8-plex immunoassay, comprising antigens used in clinical serology for diagnosis of ARF (SLO, DNase B, SpnA), and 5 conserved putative GAS vaccine antigens (Spy0843, SCPA, SpyCEP, SpyAD, Group A carbohydrate), to characterize antibody responses in sera from New Zealand children with a range of clinically diagnosed GAS disease: ARF (n = 79), GAS-positive pharyngitis (n = 94), GAS-positive skin infection (n = 51), and matched healthy controls (n = 90). Results: The magnitude and breadth of antibodies in ARF was very high, giving rise to a distinct serological profile. An average of 6.5 antigen-specific reactivities per individual was observed in ARF, compared to 4.2 in skin infections and 3.3 in pharyngitis. Conclusions: ARF patients have a unique serological profile, which may be the result of repeated precursor pharyngitis and skin infections that progressively boost antibody breadth and magnitude. Abstract : A multiantigen analysis using a novel 8-plex assay revealed a distinct serological profile in rheumatic fever patients, characterized by increases in both the magnitude and breadth of group A Streptococcus antibodies, compared to children with precursor pharyngeal and skin infections. Graphical Abstract: